Vplyv predĺženia latencie transkraniálnych motorických evokovaných potenciálov v korelácií so znížením amplitúdy počas spinálnych operácií s použitím intraoperačného neurofyziologického monitoringu na prognózu pooperačného neurologického deficitu - Beňuška, J; Čembová, N; Naser, Y; Žabka, M; Pasiar, J; Švec, A (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2020)
PURPOSE OF THE STUDY This retrospective study investigated the significance of a combination of peak latency of waveform amplitude and waveform amplitude in association with spinal deformities. The correlation with postoperative neurologic deficit was evaluated too. MATERIAL AND METHODS Between January 2007 and January 2018, a group of 113 patients was evaluated in the study who underwent spine surgery using intraoperative neurophysiological monitoring (IONM) focusing on transcranial motor evoked potential (tc-MEP) monitoring. The average age of the patients was 30 years. Tc-MEPs were recorded bilaterally from tibialis anterior muscle and the abductor hallucis muscle in 88 patients without neurological deficit and in 25 patients with neurological deficit. The peak latency of waveform amplitude was defined as the period from stimulation until the waveform amplitude reached its peak. The correlation with postoperative neurological deficit was examined separately for latency delays of 5% and 10% or more and in combination with a decrease in amplitude of 70% or more. We used the presence-absence paradigm to evaluate the disappearance of previously present tc-MEPs and amplitude latency delays. The correlation with the deterioration of amplitudes from baseline or the elevation of thresholds was not used. Statistical tests were used to investigate the changes. The cases in our study with significant tc-MEP alerts were reviewed against the evidence-based response checklist. RESULTS Of 113 patients, the decrease in amplitude of 70% or more was identified in the neurological deficit group in 64% vs. 36% in the normal neurological group (p < 0.001). The neurological deficit was observed in 7.96% of patients postoperatively. A decrease in intraoperative amplitude of 70% or more from previously present tc-MEP occurred in 40 cases, with 89% sensitivity, 64% specificity, 36% false positive rate (FPR), and 20% positive predictive value (PPV) for prediction of postoperative neurological deficit. The amplitude latency peak delay of 10% or more was observed in 41 cases from the group of patients with postoperative neurological deficit, with 100% sensitivity, 64% specificity, 36% FPR and 22% PPV. A combination of a decrease in amplitude of 70% or more from the previously present tc-MEP and a delay in amplitude latency peak of 10% or more resulted in 100% sensitivity, 49% specificity, 51% FPR and 10% PPV in the group of postoperative neurological deficit patients. DISCUSSION Intraoperative tc-MEP alarm points have previously focused mainly on waveform amplitude. In our series, a criterion of an amplitude decrease of 70% or more from previously present tc-MEP was set as the alarm point. No alarm criterion for delay of peak latency of waveform amplitude was set before. We set a latency peak delay of 5% or more and 10% or more of waveform amplitude compared with the previously present tc-MEP as alarm criteria. This is the first study exploring the issue. We demonstrated the efficacy of latency peak of waveform amplitude together with the decrease of waveform amplitude. Another study found similarities in the decrease of amplitude of 70 % or more from baseline and the delay in amplitude latency of 10% or more from baseline; with 86% sensitivity, 98% specificity, 2% FPR and 86% PPV (1). CONCLUSIONS In conclusion, we investigated the efficacy of a change of peak latency delay of waveform amplitude in tc-MEP monitoring. The utilizing of the peak latency delay of waveform amplitude value resulted in high sensitivity up to 100 % and allows reduction of the FPR and an increase of the PPV. Further studies should set the alarm criteria more precisely for the waveform amplitude latency peak delay to achieve more effective spinal cord tc-MEP monitoring. Our concept of findings supports the neurophysiological monitoring findings in other studies. Key words: monitoring, IONM, intraoperative neurophysiological monitoring, tc-MEP, motor evoked potential, transcranial, amplitude, latency, peak.
Keywords: dospělí; neurochirurgické výkony; intraoperační neurofyziologická monitorace; Incidence; lidé; retrospektivní studie; Evoked Potentials, Motor; incidence; Intraoperative Neurophysiological Monitoring; Neurosurgical Procedures; Retrospective Studies; Adult; motorické evokované potenciály; Humans